Fretting wear behaviour of ultrafine-grained copper produced by cryogenic temperature extrusion machining. Issue 8 (24th May 2023) - Zhang, Baoyu; Zeng, Yuning; Pang, Xueqin; Deng, Wenjun
Abstract : Cryogenic temperature extrusion machining (CT-EM), as a new process, was first applied for preparing ultrafine-grained (UFG) copper strips. The microstructure evolution and mechanical properties (hardness and fretting wear) were characterised by electron backscatter diffraction and transmission electron microscopy methods. Refined grains (450 nm) and high dislocation density could be obtained by CT-EM because of effectively suppressing heat generation and the annihilation of dislocations. As a result, the CT-EM sample exhibited enhanced fretting wear properties, e.g. a much lower friction coefficient (reducing 0.1–0.2) and a lower wear loss (decreasing 32–45%) were achieved due to its enhanced hardness and refined microstructure. In-depth, the delamination and oxidation wear proved to be the primary wear mechanism of the CT-EM sample under dry wear conditions.